Measurements of the production cross-section for a Z boson in association with b-jets in proton-proton collisions at √s = 13 TeV with the ATLAS detector - Fiolhais, M. C. N. (2020)
This paper presents a measurement of the production cross-section of a Z boson in association with b-jets, in proton-proton collisions at s = 13 TeV with the ATLAS experiment at the Large Hadron Collider using data corresponding to an integrated luminosity of 35.6 fb−1. Inclusive and differential cross-sections are measured for events containing a Z boson decaying into electrons or muons and produced in association with at least one or at least two b-jets with transverse momentum pT> 20 GeV and rapidity |y| < 2.5. Predictions from several Monte Carlo generators based on leading-order (LO) or next-to-leading-order (NLO) matrix elements interfaced with a parton-shower simulation and testing different flavour schemes for the choice of initial-state partons are compared with measured cross-sections. The 5-flavour number scheme predictions at NLO accuracy agree better with data than 4-flavour number scheme ones. The 4-flavour number scheme predictions underestimate data in events with at least one b-jet.